2015
DOI: 10.1038/srep15251
|View full text |Cite
|
Sign up to set email alerts
|

Iodine source apportionment in the Malawian diet

Abstract: The aim of this study was to characterise nutritional-I status in Malawi. Dietary-I intakes were assessed using new datasets of crop, fish, salt and water-I concentrations, while I status was assessed for 60 women living on each of calcareous and non-calcareous soils as defined by urinary iodine concentration (UIC). Iodine concentration in staple foods was low, with median concentrations of 0.01 mg kg−1 in maize grain, 0.008 mg kg−1 in roots and tubers, but 0.155 mg kg−1 in leafy vegetables. Freshwater fish is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 72 publications
2
41
2
Order By: Relevance
“…A recent spot survey of adult women in Malawi living on calcareous (n = 59) and non-calcareous soils (n = 59) found that the median creatinine-corrected UIC was 203 μg L −1 . However, there was a 14 % prevalence of I deficiency (UIC <100 μg L −1 ) but 21 % prevalence of excess (UIC >300 μg L −1 ) [48]. Thus, high household salt supplies or I concentration in salt might be contributing to excessive I intakes, risking hypo-and hyper-thyroidism.…”
Section: Interventions To Improve Dietary Micronutrient Suppliesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent spot survey of adult women in Malawi living on calcareous (n = 59) and non-calcareous soils (n = 59) found that the median creatinine-corrected UIC was 203 μg L −1 . However, there was a 14 % prevalence of I deficiency (UIC <100 μg L −1 ) but 21 % prevalence of excess (UIC >300 μg L −1 ) [48]. Thus, high household salt supplies or I concentration in salt might be contributing to excessive I intakes, risking hypo-and hyper-thyroidism.…”
Section: Interventions To Improve Dietary Micronutrient Suppliesmentioning
confidence: 99%
“…The present study estimated dietary mineral element supplies at household levels in Malawi by combining food supply data captured in the IHS3 [28] with locallygenerated food crop composition data [18,48]. This compares with previous efforts to quantify the prevalence of inadequate element intakes at wide scales in Malawi on the basis of national-level food supply data captured in Food Balance Sheets (FBSs) published by the FAO matched with published or local composition data [5,9,10,13,18,22,27,49,50] or food consumption from household surveys matched with published composition data [29,30].…”
Section: Comparison With Previous Estimates Of Dietary Nutrient Suppliesmentioning
confidence: 99%
“…In addition, deficiency of I is likely to affect individuals not consuming adequately iodised salt (Kalimbira et al 2005;Joy et al 2015b;Watts et al 2015) and anaemia is widespread, which may be partly due to dietary Fe deficiency (WHO 2008). In contrast, dietary deficiencies of Cu and Mg are unlikely to affect the majority of the population of Malawi due to adequate supplies via the staple crop maize.…”
Section: Introductionmentioning
confidence: 99%
“…68 However, the Biomarkers of Nutrition for Development (BOND) review for iodine suggested that biomonitoring results determined by urinary iodine and food composition tables should be calculated using ICP-MS as iodine is typically present in the parts-per-billion (µg kg -1 ) range and is considered undetectable by less sophisticated analytical methods. 9,69…”
Section: Spectrophotometric Analysismentioning
confidence: 99%
“…4,8 In addition, excessive intake, >300 µg day -1 , can also cause hyper/hypo-thyroidism, euthyroid goitre or thyroid autoimmunity. 6,9 To date, dietary supplementation, by means of iodised salt, has proved to be an efficient method of reducing the global prevalence of IDD. 4 However, this approach is associated with a number of issues including inadequate monitoring of iodine concentrations in fortified salt, as such, approximately one-third of households lack access to adequately iodised salt.…”
Section: Introductionmentioning
confidence: 99%